2004
DOI: 10.1007/s00105-004-0785-5
|View full text |Cite
|
Sign up to set email alerts
|

Herpes-simplex-Virusinfektionen

Abstract: The herpes simplex viruses type 1 and 2 (HSV 1 and 2) as typical members of the larger herpes virus group have the tendency to become latent after an inapparent primary infection. They are transmitted from person to person during episodes of reactivation. HSV 1 and 2 usually cause harmless mucosal infections. Usually HSV are kept in check by the immune system. An impaired immune response leads to HSV infections which can be life-threatening. Genital HSV infections are an important cause of genital ulcerations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0
5

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
0
9
0
5
Order By: Relevance
“…In the immunocompromised host, however, mucocutaneous lesions can be extensive or appear at unusual sites with atypical presentation [1,2] thus posing a diagnostic challenge, as shown in the following case.…”
mentioning
confidence: 87%
“…In the immunocompromised host, however, mucocutaneous lesions can be extensive or appear at unusual sites with atypical presentation [1,2] thus posing a diagnostic challenge, as shown in the following case.…”
mentioning
confidence: 87%
“…HSV infection is a well-known, chronic persistent viral infection of varying recurrence rate [1]. It has been reported that HSV can be the cause of esophagitis, as seen in immunodeficient patients under therapeutic immunosuppression [2, 3].…”
Section: Introductionmentioning
confidence: 99%
“…HSV manifestations after transplantation have been described; however, usually a time delay between organ transplantation and HSV infection – corresponding with the time necessary for the achievement of full therapeutic immunosuppression – is seen. The herpes virus group consists of the Herpes zoster virus and the Herpes simplex virus [1, 4], the former occurring much more often as a painful post-transplant infection [5, 6, 7]. Infections or recurrences of HSV after transplantation are much more uncommon and comprise case reports describing esophagitis and nephritis [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Bei älteren und immunsupprimierten Menschen können disseminierte Infektionen auftreten. Rekurrierende Infektionen lassen sich mit Triggerfaktoren wie Fieber, Sonnenlicht oder Stress sowie konsumierenden Erkrankungen und Tumoren in Zusammenhang bringen[10].…”
unclassified